ANALYSIS OF THE EMERGENCE OF LEADERSHIP AS A SOCIO-PSYCHOLOGICAL PHENOMENON - Vladislav Khlanovskyi (Публічне управління та регіональний розвиток)
The article is devoted to the analysis of the views of foreign scientists on the issue of management effectiveness and the requirements for leadership as a certain social phenomenon.